THE REPRESENTATION OF A BLASPHEMY PROTEST IN JAKARTA IN LOCAL AND INTERNATIONAL PRESS - Al Fajri, Muchamad Sholakhuddin (Universitas Pendidikan Indonesia, 2018)
The way political protests and civil (dis)order are reported in news discourse has been of interest to critical linguists (e.g. Hart, 2014; Brindle, 2016). Representations of an event in the media are typically influenced by political stances of news institutions and therefore representations of the same protest can be different in different news media, depending on the ideological framework in which they operate. This present study differs from the previous research in the sense that its data are taken from several news media in the country where the protest occurs or local newspapers, and from international or foreign newspapers which seem to have less political motives. It aims to investigate the representation of a blasphemy protest in Jakarta in both local and international press by using transitivity and van Leewuen’s social actor representation (SAR) model. The data were taken from five Indonesian news texts and five International news articles. The findings suggest that the International newspapers have a tendency to delegitimate the protest by portraying it as discrimination towards minorities and a benefit for terrorist groups. Additionally, they construct the protesters as extremists and a source of clashes and violence. On the other hand, although the Indonesian news media also appear to delegitimate the protest and the protesters, the constructions are not as radical as the foreign media.